One‐Step Fabrication of Perovskite‐Based Upconversion Devices. Issue 9 (17th June 2020) - Wieghold, Sarah; Bieber, Alexander S.; Lackner, Jens; Nienhaus, Karin; Nienhaus, G. Ulrich; Nienhaus, Lea
Abstract: Device fabrication methods for applications in upconversion processes using perovskite thin films have suffered from reproducibility and scalability issues, which prevent the upscaling of this technology. In this contribution, we developed a perovskite‐based upconversion device approach where the triplet annihilator is added in situ to the antisolvent and investigated the effect of the device fabrication procedure on the properties of our device. By comparing the properties of a device based on our new fabrication approach with the existing bilayer procedure, we seek to shed light on the underlying optoelectronic processes influenced by the different fabrication methods, while further advancing possible device architectures for upconversion devices. Device characterization by optical methods, X‐ray diffraction and atomic force microscopy revealed that the in situ fabricated devices match the performance or even outcompete our previously developed bilayer devices while significantly simplifying the device fabrication. In particular, we find that the developed one‐step fabrication technique enables intercalation of the upconverting layer into the perovskite film prior to annealing, resulting in a larger interface thus, more efficient charge extraction. Abstract : Taking it one step at a time : Perovskite‐based solid‐state upconversion devices are fabricated in situ by adding the upconverter directly to the antisolvent. Device characterization indicates that the device performance rivals the performance of previous bilayer devices, while significantly simplifying the fabrication method.